NILAI PENDIDIKAN DALAM RITUAL SAPAT TAUN - Margareta, Yustina Yuyu; Saputra, Ardi Wina (Prosiding Seminar Nasional Bahasa Ibu, 2025)
This research aims to find educational values in the Sapat Taun Ritual. The Sapat Taun Ritual is a typical ritual of the people of Silat Hulu Hamlet, Bantansari, Marau, Ketapang, West Kalimantan. The literature study showed the lack of studies on this ritual. Therefore, researchers tried to explore the educational values hidden in the rites and symbols of the Sapat Taun ritual. This research method is qualitative with an ethnographic approach. The type of research is ethnopedagogy. The source of data in this study is the perpetrator of the Sapat Taun Ritual from Silat Hulu Hamlet, Batansari, Marau, Ketapang, West Kalimantan. Data collection techniques were conducted by interview and observation. Data analysis was done by symbol and language analysis. The results of this study indicate that there are 7 symbols and 7 rites in the Sapat Taun Ritual that have educational value. The seven symbols and seven rites are presented further in this study.